Implementation of Islamic Religious Education in Inclusive Schools: Historical Study of Islamic Education in Muzdalifah Special School Medan - Muhammad Sapii Harahap (Edumaspul: Jurnal Pendidikan, 2024)
This study aims to determine the development of Special School C Muzdalifah, 2) to determine the curriculum and teaching methods of Special School C Muzdalifah, and 3) to determine the Implementation of Islamic Religious Education at Special School C Muzdalifah. In this study the author uses a historical method or historical method. The historical method consis of data collection, source criticism, interpretation and finally historiography. The research approaches used in this study are the geographical approach, sociological approach, educational approach and historical education. The results of this study are 1) Special School (SLB) C Muzdalifah is an educational unit that is managed in an integrated manner (one roof) consisting of SDLB, SMPLB, and SMALB. Based on its geographical location, SLB C Muzdalifah is located at Latitude 3 Longitude 98 which is near the Medan city crossroads, North Sumatra. Initially, before changing its name to an educational unit, SLB C Muzdalifah was established as a halfway house for street children and scavengers. They were given an education and skills so that the Foundation Management found children who were physically good and good but experienced intellectual delays. The Foundation Mother was motivated to collect mentally retarded students to be given education so that the education office gave advice and recommendations and gave permission for the establishment of a special school in 2000 so that with the passage and development of time, SLB C Muzdalifah was established. 2) The curriculum used at SLB C Muzdalifah is the independent curriculum. In the implementation of this curriculum, children are given the opportunity to develop themselves with their desires and can develop their potential, and teachers are only facilitators. and 3) Implementation of Islamic Religious Education at Special School C Muzdalifah, namely a) Learning and Practicing Prayer, b) Learning Morals, c) Learning pronunciation and writing of hijaiyyah letters, d) memorizing prayers, and muroja'ah Al-Quran.